PERBAIKAN KUALITAS PRODUK CANGKUL DENGAN METODE SIX SIGMA (DMAIC) DI BLKK AL-INSAN - Nugraha, Akbar; Kusumawati, Aulia (Jurnal Intent: Jurnal Industri dan Teknologi Terpadu, 2024)
BLKK Al – insan is a company that produces hoe products located in Environment. Karotek RT/RW 001/002.Kalitimbang village Cibeber district Cilegon city. Cilegon City with the main raw material of iron plate and other supporting tools. BLKK Al - Insan is very hopeful in creating products that allow it to compete well in terms of quality in the market and wants a 3% defect standard in its production. In the production process of hoe products BLKK Al - insan has defect problems, namely Distortion, Porosity and Undercut which can cause problems in product quality in the targeted production amount and has a defect percentage of 23% in 4 months. The purpose of this study is to apply the si sigma method (DMAIC) to reduce product defects and determine the factors that cause product defects and provide alternative efforts to improve product quality. Based on the analysis result DMAIC obtained 3 critical to quality that’s is Distorsi, Porosity and Undercat, and obtained the average initial value DPMO 763,8 (2,94) after improvement, the DPMO value becomes 644.4 and the sigma level has increased to 3.02 and the defect percentage value becomes 19% based on the process improve using the kaizen method by proposing to use 5w+1H, Five M Cheecklist and Five Step Plan and developing standard operating procedures for the production process can determine the DPMO value and increase the six sigma value.